Transformational Leadership And Perceived Organizational Support On Innovative Work Behavior : The Mediating Role Of Employee Engagement At Pegadaian Dinoyotangsi Surabaya Sub-Branch - Nabilla Mayreza Putri; Hujjatullah Fazlurrahman (Lavish Opulent Education, 2025)
This study aims to examine and analyze the effect of transformational leadership and perceived organizational support on innovative work behavior through employee engagement as a mediating variable at PT. Pegadaian Dinoyotangsi Surabaya Sub-Branch. Using Saturated sampling technique as many as 49 respondents. The analysis used in this research is SEM(structural equation modeling) and PLS (partial least square) with the aid of SmartPLS4 software. The result of this study explain that transformational leadership has a positive effect on innovative work behavior. Perceived organizational support has no effect on innovative work behavior. Employee engagement has a positive effect on innovative work behavior. Tranformational leadership affects employee engagement. Perceived organizational support affects employee engagement. Employee engagement does not mediate the relationship between transformational leadership and innovative work behavior. Employee engagement mediates the relationship between perceived organizational support and innovative work behavior.